Effect of Dietary Supplementation of Marigold (Tagetes erecta) Petal Powder on Yolk Pigmentation, Feed Efficiency and Cost Economics in Desi Layers - Hirwani, Roshni; Kumari, Kiran; Archana; Pal, Prasanna; Gendley, M. K. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was carried out from January to June, 2023 at the Poultry Instructional and Demonstration Unit (PIDU), College of Veterinary Science and Animal Husbandry, Anjora, Durg, Chhattisgarh, India to evaluate the effect of dietary supplementation of marigold (Tagetes erecta) petal powder (MPP) on yolk pigmentation, feed intake, body weight gain, feed conversion ratio (FCR), and cost economics in desi layer birds. Thirty‑six 30‑week‑old desi layers were randomly allocated into three dietary treatments: control (T0), 2% MPP (T1), and 4% MPP (T2), each with three replicates of four birds, for six weeks. Feed intake, body weight gain, FCR, yolk colour (Roche Yolk Colour Fan), and economic parameters were recorded. Results indicated that MPP supplementation had significantly improved yolk pigmentation and FCR. Birds in the 2% MPP group had exhibited optimal performance with higher egg production, improved feed efficiency, and profitability compared to control and 4% MPP groups. Economic analysis revealed that despite slightly higher feed costs, MPP inclusion had enhanced gross returns and benefit‑cost ratio, particularly in the 2% group. These findings confirmed that marigold petals, rich in lutein and zeaxanthin, had served as effective natural pigments and functional feed additives. The study concluded that dietary inclusion of marigold petal powder at 2% had been a cost‑effective natural alternative to synthetic pigments for enhancing yolk colour, feed efficiency, and profitability in desi layers under semi‑intensive production systems.